The Host Autophagy During Toxoplasma Infection - Wu, Minmin; Cudjoe, Obed; Shen, Jilong; Chen, Ying; Du, Jian (Frontiers in Microbiology, 2020)
Autophagy is an important homeostatic mechanism, in which lysosomes degrade and recycle cytosolic components. As a key defense mechanism against infections, autophagy is involved in the capture and elimination of intracellular parasites. However, intracellular parasites, such as Toxoplasma gondii, have developed several evasion mechanisms to manipulate the host cell autophagy for their growth and establish a chronic infection. This review provides an insight into the autophagy mechanism used by the host cells in the control of T. gondii and the host exploitation by the parasite. First, we summarize the mechanism of autophagy, xenophagy, and LC3-associated phagocytosis. Then, we illustrate the process of autophagy proteins-mediated T. gondii clearance. Furthermore, we discuss how the parasite blocks and exploits this process for its survival.